2015
DOI: 10.3748/wjg.v21.i48.13566
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin correlated with endoscopic remission for Asian inflammatory bowel disease patients

Abstract: fC correlated with both CDEIS and UCEIS. fC could be used as a predictor of endoscopic remission for Asian IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 32 publications
8
33
0
1
Order By: Relevance
“…Fecal calprotectin, a protein derived from neutrophils, is markedly elevated in infectious and inflammatory conditions, including IBD, and correlated well with endoscopic activity in IBD patients in a study conducted Taiwan 112113. Patients with endoscopically and histologically active UC have higher fecal calprotectin levels than those with mildly active or inactive UC, and calprotectin concentration correlates positively with advancing histological inflammation and negatively with endoscopic remission 114115. As a predictor of relapse in UC, studies have shown the sensitivity and specificity of calprotectin to be approximately 90% and 80%, respectively 116117.…”
Section: Resultsmentioning
confidence: 95%
“…Fecal calprotectin, a protein derived from neutrophils, is markedly elevated in infectious and inflammatory conditions, including IBD, and correlated well with endoscopic activity in IBD patients in a study conducted Taiwan 112113. Patients with endoscopically and histologically active UC have higher fecal calprotectin levels than those with mildly active or inactive UC, and calprotectin concentration correlates positively with advancing histological inflammation and negatively with endoscopic remission 114115. As a predictor of relapse in UC, studies have shown the sensitivity and specificity of calprotectin to be approximately 90% and 80%, respectively 116117.…”
Section: Resultsmentioning
confidence: 95%
“…United Kingdom 5983 IBD/Healthy 100 95/91 Diagnosis Dhaliwal et al 21 United Kingdom 88 IBD/IBS 100 97/76 Distinguish IBD from IBS D'Incà et al 22 Italy 46 UC 80 78/70 Active disease Xiang et al 23 China 66 UC/Healthy 50 79/92 Active disease D'Haenset al 24 The Netherlands 126 UC/IBS 250 71/100 Active disease Schoepfer et al 16 Switzerland 228 UC/Healthy 57 91/90 Active disease Samant et al 12 India 32 UC 800 96/71 Active disease Lobatón et al 25 Spain 123 UC 250 74/90 Remission Lin et al 26 Taiwan 52 UC 191 88/75 Remission Dhaliwal et al 21 United Kingdom 88 IBD/IBS 250 90/76 Remission Costa et al 27 Italy 41 UC 150 89/82 Relapse Tibble et al 28 England 80 IBD 50 90/83 Relapse D'Inca et al 29 Italy Optimal cut-off value of fecal calprotectin: An unsolved issue?…”
mentioning
confidence: 99%
“…First, the effectiveness of serum SHAP-HA complex as a biomarker remains unclear. Other promising biomarkers, for example, calprotectin, have already been shown to be useful in screening for suspected IBD, in predicting endoscopic remission, and in predicting the risk of relapse [21,22,23]. However, even with calprotectin, an essential first step is to demonstrate a difference between healthy controls and IBD patients [24].…”
Section: Discussionmentioning
confidence: 99%